Statistical thermodynamics of hydrocarbon fluids: Scaling parameters and their group contributions - (:unkn) unknown (My University, 1995)
We have analysed the equation of states (eos) data for five series of compounds in terms of the Simha-Somcynsky hole theory and, in this manner, obtained graph-averaged temperature, volume and pressure scaling parameters. The eos data were obtained some time ago, when several series of hydrocarbon oligomer fluids with systematically varied structures were synthesized and their eos and Newtonian viscosities determined over broad ranges of temperature and pressure. By means of suitable decomposition equations, individual group attraction energy and repulsion volume quantities have now been derived. These compounds include saturated and unsaturated rings. The approach taken also yields results for branched alkanes. However, the results diverge from what would be expected from those found for the linear species. Simple linearities between group self-interaction repulsion volumes and Bondi's van der Waals volumes, and correlations of energy parameters with group-derived cohesive energy estimates are observed. The results obtained can form a basis for equation of state predictions and encourage applications of the methodology to further structures. Finally, the results lead to ideas for the investigation of correlations between rheological and thermodynamic equations of state.